National and foreign experience in the organization of distance education in higher education institutions of Uzbekistan (Eurasian Research Bulletin, 2022)
This article discusses the formation of the organizational and legal foundations of distance education, the factors hindering the formation of the legal foundations of distance education in Uzbekistan, the existing legal gaps and conflicts in national legislation, the development of organizational and institutional mechanisms for distance education. The study, analysis, generalization and implementation of the experience of foreign countries in the formation of the regulatory framework for distance education is one of the most pressing issues.